Entrepreneurial Self-Identity: Predictors and Effects Within the Theory of Planned Behavior Framework - Obschonka, Martin; Silbereisen, Rainer K.; Cantner, Uwe; Goethner, Maximilian (Journal of Business and Psychology, 2015)
To combine the identity and the theory of planned behavior (TPB) approaches to entrepreneurship, we investigated unique main effects as well as moderating effects of an entrepreneurial self-identity in the TPB-entrepreneurship framework. We also investigated predictors of an entrepreneurial self-identity.